Angiotensin‐converting enzyme inhibitors prior to scleroderma renal crisis in systemic sclerosis: A systematic review and meta‐analysis. (1st March 2022) - Xiong, Anji; Cao, Yuzi; Xiang, Qilang; Song, Zhuoyao; Zhang, Yan; Zhou, Shifeng; Qiang, Yiying; Chen, Huini; Hu, Ziyi; Cui, Hongxu; Luo, Jie; Wang, Ye; et al.
Abstract: What is known and objective: Angiotensin‐converting enzyme inhibitors (ACEIs) are widely used in the treatment of scleroderma renal crisis (SRC), and their use prior to the onset of SRC in patients with systemic sclerosis (SSc) has received wide attention in recent years. We undertook an evidence‐based approach to identify whether the use of ACEIs prior to the onset of SRC is beneficial for patients with SSc. Methods: We searched PubMed and Embase for any published studies produced between database inception and 22 October 2021. Articles obtained after using appropriate keywords were selected independently by two reviewers according to the established inclusion and exclusion criteria. Results: Nine studies were included. Pooled results indicated that using ACEIs prior to SRC was associated with a higher incidence of SRC than no ACEIs prior to SRC (RR 2.05, 95% confidence interval 1.08–3.91, p = 0.03). Compared with patients who did not use ACEIs prior to the onset of SRC, a higher proportion of patients with SRC who used ACEIs prior to its onset had a poorer prognosis (RR 1.46, 95% confidence interval 1.20–1.78, p < 0.01). The difference in mortality between patients who used ACEIs prior to SRC onset and those who did not was not statistically significant (RR 1.12, 95% confidence interval 0.76–1.65, p = 0.57). What is new and conclusions: We recommend against using ACEIs prior to SRC in SSc patients. The use of ACEIs prior to SRC is associated with a higher incidence of SRC and poorer prognosis, especially in patients with progressive SSc or SSc‐related renal vasculopathy (SSc‐related hypertension and proteinuria). Abstract : A potential pathogenetic mechanism for SRC, and the effects of ACEIs prior to SRC.